Techno-economic analysis of an optimized photovoltaic and diesel generator hybrid power system for remote houses in a tropical climate - Ismail, M.S.; Moghavvemi, Mahmoud; Mahlia, T.M.I. (Elsevier, 2013)
A techno-economic analysis and the design of a complete hybrid system, consisting of photovoltaic (PV) panels, a battery system and a diesel generator as a backup power source for a typical Malaysian village household is presented in this paper. The specifications of the different components constructing the hybrid system were also determined. A scenario depending on a standalone PV and other scenario depending on a diesel generator only were also analyzed. A simulation program was developed to simulate the operation of these different scenarios. The scenario that achieves the minimum cost while meeting the load requirement was selected. The optimal tilt angle of the PV panels in order to increase the generated energy was obtained using genetic algorithm. In addition, sensitivity analysis was undertaken to evaluate the effect of change of some parameters on the cost of energy. The results indicated that the optimal scenario is the one that consists of a combination of the PV panels, battery bank and a diesel generator. Powering a rural house using this hybrid system is advantageous as it decreases operating cost, increases efficiencies, and reduces pollutant emissions.